Evidence-based allocation in global health: lessons learned for Germany - Anna Minasyan (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
This paper studies evidence-based aid allocations in global health with the aim to identify lessons learned for Germany as a donor for bilateral and multilateral aid programmes. At the same time, it contributes to the conceptualisation of evidence-based aid by defining two types of evidence, practical and scientific, where the former makes use of discretionary information to support the financing of aid projects, while the latter relies on the evidence from rigorous (scientific) research. This desk-study combined with interviews shows that practical evidence is commonly used in health aid allocations, while scientific evidence is used mainly at The Global Fund and is included in World Health Organization guidelines for health policies worldwide. Furthermore, benefits of and barriers to scientific evidence-based allocation are discussed, while recommendations are provided with the aim of developing a scientific, evidence-based aid approach for a bilateral donor in health aid.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Wirksamkeit und Evaluierung